Regional Financial Performance Before and After The Regional Autonomy in Special Region of Yogyakarta - Djoko Susanto; Rudy Badrudin; Nuri Marlia (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
Abstract The purpose of this study to examines and analyze differences the financial performance of local governments before and after decentralization. Through regional autonomy, local government has the authority to explore the role of the allocation of income and perform independently in setting development priorities. It is based on Law No. 23/2014 on Regional Government and Law No. 33/2004 on Financial Balance between Central and Local Government. The sample in this study were all districts in Special Region of Yogyakarta (DIY) in the period of 1994 to 2015. The sample used is districts in DIY namely Bantul, Gunungkidul, Kulon Progo, Sleman Regency, and Yogyakarta City. Data used in this research is secondary data. Data analysis using Paired Sample T - Test. These results indicate that there is no difference of fiscal decentralization degrees in districts in DIY before and after regional autonomy; there is no difference of regional financial independence ratio in districts in DIY before and after regional autonomy; and there is differences of regional financial in harmony ratio in districts in DIY before and after regional autonomy.